2021
DOI: 10.3389/fonc.2021.797968
|View full text |Cite
|
Sign up to set email alerts
|

Exosome Component 4 Promotes Epithelial Ovarian Cancer Cell Proliferation, Migration, and Invasion via the Wnt Pathway

Abstract: BackgroundOf gynecologic malignancies, ovarian cancer is the leading cause of death, mainly due to the lack of sensitive tumor markers, which means it almost always presents at an advanced stage. Exosome Component 4 (EXOSC4) is involved in RNA degradation, but its role in epithelial ovarian cancer (EOC) is unclear.MethodsThe expression levels of EXOSC4 in EOC and normal ovarian tissue specimens were determined by immunohistochemical staining. The overall survival (OS) and progression-free survival (PFS) of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Similarly, low expression of PDIA4 has been reported to be associated with shorter survival in ovarian tumors, especially in drugresistant tissues [29,30]. Another interesting point is that high EXOSC4 expression promotes malignant features of OC via the Wnt pathway and correlates with higher FIGO stage and pathological grade, although it is a protective factor in our signature [31]. Although the relationship between other genes and OC has not been adequately studied, they have been reported to play a role in other cancers.…”
Section: Discussionmentioning
confidence: 76%
“…Similarly, low expression of PDIA4 has been reported to be associated with shorter survival in ovarian tumors, especially in drugresistant tissues [29,30]. Another interesting point is that high EXOSC4 expression promotes malignant features of OC via the Wnt pathway and correlates with higher FIGO stage and pathological grade, although it is a protective factor in our signature [31]. Although the relationship between other genes and OC has not been adequately studied, they have been reported to play a role in other cancers.…”
Section: Discussionmentioning
confidence: 76%
“…Only articles published in English were included. After the exclusion of duplicate, irrelevant journal articles and non-journal articles, 39 articles on exosome and EOC were selected for bibliometric analysis; 36 of which were original articles ( Zhang et al, 2016a ; Meng et al, 2016b ; Zhang et al, 2016b ; Labani-Motlagh et al, 2016 ; Ying et al, 2016 ; Chen et al, 2017 ; Hu et al, 2017 ; Li et al, 2017 ; Wu et al, 2017 ; Chen et al, 2018 ; Qiu et al, 2018 ; Zhang et al, 2018 ; Zhou et al, 2018 ; Zhang et al, 2019a ; Keserű et al, 2019 ; Tang et al, 2019 ; Zhu et al, 2019 ; Cheng et al, 2020 ; Li et al, 2020 ; Lu et al, 2020 ; Luo and Gui, 2020 ; Maeda et al, 2020 ; Masoumi-Dehghi et al, 2020 ; Alharbi et al, 2021 ; Xiong et al, 2021a ; Cai et al, 2021 ; Gao et al, 2021 ; Li et al, 2021 ; Liu et al, 2021 ; Ma et al, 2021 ; Zhu et al, 2022a ; Chen et al, 2022 ; Jeon et al, 2022 ; Lai et al, 2022 ; Yang et al, 2022 ), and the rest of them were review articles ( Li and Wang, 2017 ; Lucidi et al, 2020 ; Shiao et al, 2021 ). The first English article is “Characterization of exosomes derived from ovarian cancer cells and normal ovarian epithelial cells by nanoparticle tracking analysis” in 2015 ( Zhang et al, 2016a ).…”
Section: Resultsmentioning
confidence: 99%
“…The alteration of EXOSC4 was associated with the OS and PFS pancreatic cancer patients [20]. Downregulation of EXOSC4 can inhibit cancer cell migration and invasion [21,22]. Taniue et al also showed that EXOSC4 knockdown led to the reduction in the viability of pancreatic and colorectal tumor cells [20].…”
Section: Discussionmentioning
confidence: 99%